2011
DOI: 10.5194/bg-8-3793-2011
|View full text |Cite
|
Sign up to set email alerts
|

Particle-reactive radionuclides (<sup>234</sup>Th, <sup>210</sup>Pb, <sup>210</sup>) as tracers for the estimation of export production in the South China Sea

Abstract: 226 Ra is commonly observed in the upper water column. Sinking fluxes of total mass, POC, PIC, PN, 234 Th, 210 Pb, and 210 Po measured at the euphotic depth were low in summer-fall and high in winter-spring, reflecting the seasonal variability of biological pumping. Excluding the suspiciously low primary productivity data point in July 2007, a relatively high e-ratio of 0.28-0.69 was estimated by the ratio of the POC flux at the euphotic depth and the integrated primary productivity. The ratios of 234 Th, 210… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 66 publications
4
35
1
Order By: Relevance
“…In addition, an average ratio of 4.0 ± 1.6 (1SD, n = 77) μmol dpm −1 for suspended particle POC/ 234 Th was determined at the depth of 150 m in the basin regime. This ratio is remarkably close to the trap‐derived POC/ 234 Th ratios of 4.8 ± 1.8 μmol dpm −1 reported at the same depth horizon in this region [ Wei et al ., ], despite that dissolved 234 Th preferentially absorbs to QMA filters during particle filtration and thus may cause a bias in POC/ 234 Th ratio reported here [e.g., Benitez‐Nelson et al ., ; Rutgers van der Loeff et al ., ].Overall, POC export fluxes in the basin area are low and relatively uniform (Figure ). The average POC export fluxes in the four surveys are 7.7 ± 2.7 (n = 22), 4.3 ± 1.4 (n = 26), 9.7 ± 4.0 (n = 12), and 4.5 ± 2.0 (n = 20) mmol m −2 d −1 , respectively.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, an average ratio of 4.0 ± 1.6 (1SD, n = 77) μmol dpm −1 for suspended particle POC/ 234 Th was determined at the depth of 150 m in the basin regime. This ratio is remarkably close to the trap‐derived POC/ 234 Th ratios of 4.8 ± 1.8 μmol dpm −1 reported at the same depth horizon in this region [ Wei et al ., ], despite that dissolved 234 Th preferentially absorbs to QMA filters during particle filtration and thus may cause a bias in POC/ 234 Th ratio reported here [e.g., Benitez‐Nelson et al ., ; Rutgers van der Loeff et al ., ].Overall, POC export fluxes in the basin area are low and relatively uniform (Figure ). The average POC export fluxes in the four surveys are 7.7 ± 2.7 (n = 22), 4.3 ± 1.4 (n = 26), 9.7 ± 4.0 (n = 12), and 4.5 ± 2.0 (n = 20) mmol m −2 d −1 , respectively.…”
Section: Discussionmentioning
confidence: 94%
“…The average POC export fluxes in the four surveys are 7.7 ± 2.7 (n = 22), 4.3 ± 1.4 (n = 26), 9.7 ± 4.0 (n = 12), and 4.5 ± 2.0 (n = 20) mmol m −2 d −1 , respectively. These values are within the range of POC export flux that was reported in the same region [e.g., Chen et al ., ; Wei et al ., ; Hung et al ., ]. In addition, they are also comparable to the POC export rates reported in the open oceans [e.g., Rutgers van der Loeff et al ., ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At station 91 with a deeper seafloor than 105A, the TPM contents showed the same value in euphotic and mesopelagic water, averaging 0.52 6 0.01 mg L 21 (Table 1). It has been revealed that particulate matter in the euphotic zone is rich in biogenic components (i.e., organic matter and biogenic silica) in the western SCS [Wei et al, 2011;Cai et al, 2015;Yang et al, 2015b]. During settling below the euphotic zone, organic components degrade up to >50% in the SCS [Chen et al, 1998;Yang et al, 2009]; the TPM contents would decrease in the mesopelagic layer if there were no additional inputs of particulate matter.…”
Section: Po Deficiency In Mesopelagic Watermentioning
confidence: 99%
“…In the coastal NSCS, biological production is controlled by river plume and coastal upwelling leading to a large variability of export flux over the shelf (Gan et al, 2010(Gan et al, , 2014. There is higher export flux during winter-spring in the central NSCS (Wei et al, 2011) due to the increase of nutrient fluxes by turbulent mixing and Ekman pumping . In addition, mesoscale eddies might account for some high particle fluxes in the central NSCS (Zhou et al, 2013).…”
mentioning
confidence: 99%